Unlocking the Secrets of Pheromones: Reproductive and Social Communication in Domestic Mammals - Dharani, K.; Abinaya, P.; J, Violet Beaulah; Sridevi, P.; Gnanadevi, R.; Kannan, T. A. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2024)
Pheromones play a pivotal role in the reproductive and behavioural management of livestock, influencing various physiological and behavioural responses within and across species. This review explores the application of pheromones in cattle, buffalo, sheep, goats, pigs, and equines, highlighting their significant impact on reproductive efficiency, stress reduction, and animal welfare. In cattle, pheromones are essential for estrus detection and the enhancement of maternal bonding. Similarly, in buffaloes, urinary pheromones have been identified as markers for estrus detection, aiding in overcoming the challenge of silent ovulation, while also contributing to penis erection and sperm quantity enhancement. In small ruminants such as sheep and goats, the "male effect" accelerates puberty and synchronizes estrus, which is crucial for optimizing breeding cycles. In pigs, the presence of boars accelerates puberty in gilts and reduces postpartum anestrus in sows, enhancing reproductive outcomes. Equines benefit from appeasing pheromones, which alleviate stress in foals and adult horses, particularly during transportation and other stressful events. The synthesis and application of synthetic analogs of these pheromones have demonstrated practical benefits in animal husbandry, offering promising avenues for improving reproductive performance and animal welfare. However, despite these advancements, the identification and characterization of specific pheromones across different species remain incomplete. Future research should focus on the molecular identification of these pheromones, their mechanisms of action, and the development of innovative applications to further enhance their utility in animal management.